2010
DOI: 10.1016/j.intaccaudtax.2010.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Internal audit department characteristics/activities and audit fees: Some evidence from Hong Kong firms

Abstract: a b s t r a c tThis study provides preliminary support for the notion that internal audit function assists in reducing external audit effort and fees. Data on internal audit characteristics and activities are obtained from survey respondents of Hong Kong companies and audit fee model data are acquired from their annual reports. The results of this study suggest that the external auditor of firms in Hong Kong rely on the internal audit function and subsequently charge a lower fee. Lower external audit fees are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 37 publications
2
54
0
4
Order By: Relevance
“…Prior empirical evidence indicates that the extent to which external auditors rely on the internal audit work will be greater when the IA department possesses the characteristics associated with competency (Messier & Schneider, 1988; Ho & Hutchinson, 2010). These studies focus on specific criteria used to assess the competency of the IA function, including how long the IA function has been present in the organization (Arena & Azzone, 2009), IA training programs and professional certification (Brown, 1983; Mat Zain, Subramaniam & Stewart, 2006; Ho & Hutchinson, 2010) and IA experience in auditing and accounting (Messier & Schneider, 1988; Suwaidan & Qasim, 2010).…”
Section: Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior empirical evidence indicates that the extent to which external auditors rely on the internal audit work will be greater when the IA department possesses the characteristics associated with competency (Messier & Schneider, 1988; Ho & Hutchinson, 2010). These studies focus on specific criteria used to assess the competency of the IA function, including how long the IA function has been present in the organization (Arena & Azzone, 2009), IA training programs and professional certification (Brown, 1983; Mat Zain, Subramaniam & Stewart, 2006; Ho & Hutchinson, 2010) and IA experience in auditing and accounting (Messier & Schneider, 1988; Suwaidan & Qasim, 2010).…”
Section: Background and Hypothesesmentioning
confidence: 99%
“… Ho and Hutchinson (2010) utilized several proxies of IA including size, IA staff prior experience and certification. Their results also support a negative relationship between IA and audit fees. …”
mentioning
confidence: 99%
“…Although we expect focus, expertise, and autonomy of IAFs to have an influence on the level of co-sourcing for internal audit activities, the associations we defined in our hypotheses may suffer changes depending on whether the IAF is voluntary or mandatory for specific organizations in a given institutional context. Though there is a wide range of empirical literature about the substitution or complementary effect between internal and external audit activities (Carey et al, 2000;Elliott & Korpi, 1978;Felix, Gramling, & Maletta, 2001;Hay, Knechel, & Ling, 2008;Hay, Knechel, & Wong, 2006;Ho & Hutchinson, 2010;Mohamed et al, 2012;Prawitt, Sharp, & Wood, 2011;Stein, Simunic, & O'Keefe, 1994), there are no studies, to our knowledge, examining the relationship between IAF characteristics and co-sourcing, depending on whether the IAF is voluntary or mandatory.…”
Section: Iaf Characteristics and Co-sourcing Fees To Support Internmentioning
confidence: 99%
“…The relationship between the existence of an internal audit department and audit costs has been studied by Ho and Hutchinson (2010) in the Hong Kong market. The authors concluded that there is a relationship between these two variables, i.e., the higher the internal audit effort, the lower the external audit fees.…”
Section: Determinants Of the Costs Of Audit Servicesmentioning
confidence: 99%